Optimizing the Role of Physical Education Students in Campus Organizations through Organizational Management Training - Yunarta, Arsika; Risfandi Setyawan; Guntum Budi Prasetyo (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to optimise the role of Physical Education (PE) students in campus organisations through organisational management training which is carried out in a series of DIKLAT activities of the PE Study Program Student Association (HMP). PE students, in addition to being required to have academic competence and skills in the field of sports, also need to be equipped with managerial and leadership skills to support their involvement in student organisations. Therefore, this training focused on strengthening understanding and basic skills in managing organisations effectively and professionally. The training method was conducted through interactive materials, group discussions, and simulations of managerial practices such as work program planning, decision-making, and conflict resolution in organisations. The evaluation results showed that there was a positive increase in participants' understanding and enthusiasm in participating in organisational activities, with participants' responses increasing by 80% after the training compared to before the training. This improvement was measured through pre-test and post-test questionnaires and direct observation during the activities.Thus, this training provides a real contribution in forming the character of Physical Education students who are active, responsible, and ready to become competent leaders in campus organizational environments.